2022
DOI: 10.1016/j.imu.2021.100840
|View full text |Cite
|
Sign up to set email alerts
|

Systems Biology and Bioinformatics approach to Identify blood based signatures molecules and drug targets of patient with COVID-19

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection results in the development of a highly contagious respiratory ailment known as new coronavirus disease (COVID-19). Despite the fact that the prevalence of COVID-19 continues to rise, it is still unclear how people become infected with SARS-CoV-2 and how patients with COVID-19 become so unwell. Detecting biomarkers for COVID-19 using peripheral blood mononuclear cells (PBMCs) may aid in drug development and treatment. This research aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 87 publications
(83 reference statements)
1
17
0
Order By: Relevance
“…It is generally believed that TOP2A is a prognostic indicator of NSCLC, and its level is negatively correlated with the prognosis ( Hou et al, 2017 ; Ma et al, 2019 ). In consistence with the result of our study, TOP2A has been identified as a hub gene that could govern many cellular processes by protein–protein interactions in COVID-19 patients ( Hasan et al, 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…It is generally believed that TOP2A is a prognostic indicator of NSCLC, and its level is negatively correlated with the prognosis ( Hou et al, 2017 ; Ma et al, 2019 ). In consistence with the result of our study, TOP2A has been identified as a hub gene that could govern many cellular processes by protein–protein interactions in COVID-19 patients ( Hasan et al, 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…TOP2A (AUC = 0.842) is a crucial gene in the DNA replication process during the cell cycle. It was identified as a central hub gene in a study on comparing the gene expression profiles of blood samples from patients with COVID-19 with healthy controls 64 . According to the drug-gene network constructed, it was inhibited by different classes of anti-cancers such as anthracyclines, mitotic inhibitors, anti-tumor antibiotics, and topoisomerase II inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In-silico approaches are not only less time-consuming but also cost-effective as compared to conventional drug design [29,30]. With the advancements in the field of Bioinformatics, different tools and algorithms have been advised that identify and discover the drug targets [31]. Molecular docking is one of the popular and modern in silico approaches in the field of medical research that led to the invention of new compounds by observing the pattern of the small molecule's binding to the target and hence discovering the new drug that combats the deadly diseases [32,33].…”
Section: Solvent Accessible Surface Area (Sasa)mentioning
confidence: 99%